Artificial intelligence in higher education and research: A sample of tourism academic opinions - Güven, Selda; Yılmaz Balkaner, Selin; Şahin, Bayram (Turyzm/Tourism, 2025)
The rise and swift advance of artificial intelligence technologies has led to substantial modifications in educational procedures, encompassing learning, teaching and the research process. Although possessing impactful and enabling characteristics, it is obvious that these technologies are the focal point of significant debates. This research aims to explore the opinions of tourism academics regarding the incorporation of artificial intelligence (AI) within educational and research frameworks, while also recognizing the potential benefits and obstacles associated with them. The data obtained from 15 semi-structured interviews was scrutinized using descriptive and content analysis methodologies. The analyses were carried out with the assistance of MAXQDA software. It was observed that the primary strength of AI tools lies in their rapidity, while their main weakness is the dissemination of inaccurate data. Despite the perspective that AI is incapable of substituting human contributions because it does not possess emotions, its value for reliability has gained considerable attention.